Confidential enquiries into maternal deaths in Ondo State, Nigeria - a comparative analysis - Lawal Oyeneyin; Thomas van den Akker; Oladipo Durojaiye; Ola Obaado; Francis Akanbiemu; Yetunde Olagbuji; Isaac Aladeniyi; Majeed Oyeneyin; Olajumoke Aladenola (BMC, 2019)
Abstract Background Paucity of data on state-wide maternal mortality in Nigeria hampers planning, monitoring and evaluation of the impact of interventions. The Confidential Enquiry into Maternal Deaths in Ondo State was initiated to overcome this problem. This study aimed to compare trends of maternal mortality ratios, causes of deaths, geographical distribution and other associated factors in 12-monthly reports of the Confidential Enquiry into Maternal Deaths in Ondo State. Methods Notification forms were distributed throughout the State to focal persons and medical records officers at community and facility levels, respectively. Maternal deaths, as defined in the International Classification of Diseases 10th version, were recorded prospectively over 3 years from 1st June 2012 to 30th May, 2015. Forms were submitted, collated and data analysed by a multidisciplinary review committee. Results Reported numbers of maternal deaths (and maternal mortality ratios) were 114 (253 per 100,000 births), 89 (192) and 81 (170), respectively per year, indicating a 33% reduction in maternal mortality ratio over the course of the study period. Assuming that the confidential enquiry process was the only intervention at the time aimed at reducing maternal mortality, simple linear regression with a correlation coefficient of 0.9314, showed a relationship though the difference in the values were not statistically significant (95% CI = − 184.55 to 101.55, p = 0.169). Postpartum haemorrhage and eclampsia were the leading causes of deaths. Conclusion There was a trend of reduction in maternal mortality ratio during the period of study with postpartum haemorrhage as the major cause of death. The positive association between the confidential enquiry reports and maternal mortality ratios make us recommend that our model be adopted in other states and at the federal level.